Utcaképes - Elbert, Márta (Hungary : Fekete Doboz, 2003)
The filmmakers follow one hundred homeless adults and children as they wander the streets of Budapest. What makes the authors' attitude remarkable is their ability to get close to controversial social phenomena: they search for general human values in the behavior and mentality of their chosen characters. All this depends not only on creating situations which seem to be spontaneous, but also on the filmmakers' empathetic, human approach. The film's circular structure - returning to events of certain families' life - reflects the hopeless stages which characterize this temporary way of life full of traps and specious solutions.
Verzio Film Festival Submission
Duration: 01:35:00
Keywords: Hungary